Trade and Transport Facilitation : A Toolkit for Audit, Analysis, and Remedial Action - Raven, John (Washington, DC: World Bank, 2013)
This document is an expanded version of the paper published in 2000 under the title "Trade and Transport Facilitation: An Audit Methodology." It seeks to improve the effectiveness of diagnosis and corrective activities in the field of trade and transport facilitation by providing beyond guidelines on how to carry out the preliminary audit, insights on how to go over analysis, and preparation of appropriate remedial action.